The IMF Approach to Economic Stabilization - Savastano, Miguel (IMF Working Papers; Working Paper ;, 1999)
This paper explains the IMF approach to economic stabilization. It argues that a Fund-supported program is a process, comprising six broadly defined phases, that evolves along a multiplicity of potential pathways. The paper discusses the three-pronged approach to stabilization at the core of all IMF-supported programs, stresses the iterative character of 'financial programming,' and explains the rationale for setting quantitative performance criteria for fiscal and monetary policy in IMF-supported arrangements. A main theme is that IMF-supported programs contain a great deal of flexibility to respond both to differences in circumstances and to changes in conditions in individual cases.